(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India is home to a rich tradition of drama. Even before the Indians learned about Greek play,this region may be considered the cradle of the theatrical heritage. In depicting events and people withina framework of space and time, drama is a mimetic portrayal of life that combines the real and thefantastic, art and reality. It’s like a poem and a painting rolled into one. In order to investigate thecreation of a composite vision of modern Indian subjectivity, this research project analyzes plays byTendulkar, Karnad, Mohan rakesh, and Dattani. Psychoanalysis, cultural studies, gender studies,archetypal criticism, Marxist critique, formalism, etc., have all been used in the study of contemporaryIndian play. There has been a lot of critical work done on translated Indian play and, of course, on Indiandrama in general in recent years. Due to the wide variety of critical approaches used to understand andanalyze the works of Vijay Tendulkar, Girish Karnad, Mohan Rakesh, and Mahesh Dattani, a sizable bodyof critical literature has developed around these four Indian playwrights.